Research on the Impact of Public Management Quality on Local Economic Growth in Vietnam - Trung, Ngo Sy; Hai, Nguyen Duc; Tuyen, Nguyen Van; Tung, Phuong Huu (Journal of Ecohumanism, 2024)
Local economic growth is affected by many factors, including both objective and subjective factors. This study analyzes the impact of public management quality on local economic growth in Vietnam in the period 2016-2023. Based on the inheritance and development of many previous research results, the authors apply the Cobb-Douglas function to assess the impact of government capital; consider both the individual and interactive effects between local spending and public management quality on local economic growth. The model is estimated using the system theory method (SGMM) with data collected from 63 localities (provinces and cities) in Vietnam. The research results show that both local spending and public management quality have a positive impact on local economic growth. From the results of this study, the authors propose a number of policy recommendations to improve local spending efficiency and public management to promote economic growth in Vietnamese localities.